2017
DOI: 10.1007/s00704-017-2175-9
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on building energy demands in the intra-Americas region

Abstract: It was recently reported a regional warming in the intra-Americas region where sea surface temperature exhibited increases exceeding 0.15°C/decade and an accelerated air temperature rise that could impact building energy demands per capita (EDC). Reanalysis data is used herein to quantify the impacts of these warming trends on EDC. Results of the analysis depict a Southern Greater Antilles and inland South America with a positive annual EDC rate of 1-5 kWh per year. The Intergovernmental Panel on Climate Chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Angeles et al [53] revealed that, to maintain ideal indoor building conditions at the end of the twenty-first century in the Intra-Americas region, an increased energy production and improved energy infrastructure will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Angeles et al [53] revealed that, to maintain ideal indoor building conditions at the end of the twenty-first century in the Intra-Americas region, an increased energy production and improved energy infrastructure will be required.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, there is a probability increase to develop a maximum HI between 30 and 36 ∘ C. In the business-as-usual scenario (RCP8.5), massive HWs events are projected across the whole region, particularly in Central America, Mexico, and Northern South America. Additionally, there is a variation in both HWs number and maximum amplitude distribution shape with the maximum HI shifted to the interval 36-38 ∘ C. The socioeconomic implications of these projections for the region may be significant in terms of human health and energy demand projections, as the authors recently reported [66]. …”
Section: Discussionmentioning
confidence: 88%
“…Intense HI could develop extreme HW events with a high impact on human health [27,31,35,64,65] as well as in energy demand for air conditioning systems [66]. An early warning system is relevant to mitigate possible heat strokes' impact on the population's health.…”
Section: Current Iar Climatologymentioning
confidence: 99%
See 1 more Smart Citation
“…Cooling loads in tropical areas were derived from a multi-model ensemble (Angeles et al 2017) in low to medium emissions scenarios, finding mean total increases of over 8 GW for the Caribbean region. Lebassi et al (2010) used historical records to study CDD, demand, and consumption in California, finding large sensitivity to regional scale phenomena (e.g., increased sea-breeze impacting demand near the coast).…”
Section: Introductionmentioning
confidence: 99%